PENGARUH SEBELUM DAN SESUDAH DILAKUKAN PIJAT PUNGGUNG TEKNIK COUNTERPRESSURE TERHADAP PENGURANGAN RASA NYERI IBU BERSALIN KALA I FASE AKTIF DI KLINIK BIDAN ELVIANA TAHUN 2017 - Satria, M. (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Pain is an unpleasant state of feeling. It is very subjective because the pain is differentto everyone in terms of scale or level. Pain is very disturbing and complicates more peoplethan any disease. Pain is an unpleasant sensory and emotional experience resulting fromactual or potential tissue damage. The research design used was quasy experiment with onegroup pretest-posttest appproach. The population in this study is all of maternal pain firststage of active phase since May to Agust at maternity Clinic Midwife Elviana. The sample inthis study were 20 maternal pain first stage of active phase. The sampling technique in thisresearch is consecutive sampling.The results showed the average of labor pain before thecounterpressure massage was 8,3 (severe pain) with a scale of 7-9. The mean of labor painafter the counterpressure massage was 5,1 (moderate pain) on a 3-7 scale. The data analysisshowed that the significance was less than 5 % (p = 0,000 < 0,05). So it can be concluded thatmassage counterpressure techniques effective againts the reduction of maternal pain when thefirst stage of active phase in the maternity hospital Bulan Mulya Perawang. The reseacherhope to maternity hospital Bulan Mulya Perawang this counterpressure massage can be usedas part of midwifery care as a reduction of pain in the maternal pain first stage of activephase.